Aircraft Observation of a Two-Layer Cloud and the Analysis of Cold Cloud Seeding Effect - Dong, Xiaobo; Sun, Xiaoshen; Yan, Fei; Zhang, Jiannan; Wang, Shuyi; Peng, Min; Zhu, Haipeng (Frontiers in Environmental Science, 2022)
A two-layer stratus cloud was developed under the weather of an upper-level trough and return flow in North China. King-air 350 meteorological aircraft was designated to acquire the microphysical characteristics of this cloud. Within the lower-level warm cloud, the width of cloud particle size distribution (PSD) grew larger from the cloud top to the base. The particles in the warm cloud were developed mostly through collision-coalescence process. Supercooled liquid water (SLW) was detected abundantly in the upper layer cold cloud, which were developed under the westerly trough. In this study, the cold cloud in the upper-level were targeted for AgI seeding. After the seeding, the PSD of both cloud droplets and ice crystals were broaden as SLW were consumed and developed into ice crystals.